A Helicopter Survey for Cliff-Nesting Raptors Along the Dalton Highway in Northern Alaska, 2010 - Erica H. Craig; Jim D. Herriges; Tim H. Craig (Birds)
We conducted a helicopter survey in 2010 for cliff-nesting raptors along the Dalton Highway in northern Alaska. The study area extended from the Yukon River northward ~395 km through the Brooks Range to the Arctic Plain. We documented 55 occupied raptor nesting territories, including 25 Golden Eagle (Aquila chrysaetos), 11 Gyrfalcon (Falco rusticolus), and 10 Peregrine Falcon (Falco peregrinus) territories. We also recorded vacant stick nests and raptor perch sites on cliffs. We identified more occupied eagle territories and hundreds more vacant eagle stick nests than were previously known in the study area. The average number of Golden Eagle nestlings/nesting pairs at the time of the survey was 1.5 ± 0.6. The most productive Golden Eagle pairs were located in the northern part of the study area. The number of occupied eagle territories in 2010 is far fewer than the number of eagle stick nests we recorded. Our data indicate that the distribution of nesting eagles in the 2010 study area is different than in the past. Whether this reflects changes in eagle density; a response to availability of prey, climate change, human activities, or a combination of these; or some other factor warrants further investigation. Intensive surveys along the Dalton Highway in the 1970s found no occupied nests for Peregrine Falcons or Gyrfalcons but we found 10 and 11, respectively. Therefore, the Peregrine Falcon and Gyrfalcon nests we recorded in 2010 reflect an increase in the number of known nesting pairs there.